Resource depletion rent and its implications on optimal depletion in selected oil producing countries in Southeast Asia - Wan, Leong Fee (Malaysian Agricultural Economics Association, 1984)
The allocation of natural resource rent - petroleum has assumed a new dimension in the oil producing countries of Southeast Asia in the 1970s as Production Sharing Contracts (PSC) replaces the concession system. This paper analyses the Inherent weaknesses of the major provisions of production sharing contracts, that is, cost recovery, profit sharing and production sharing all of which fail to capture what the author has conceptualised as the resource depletion rent.